The physiology efficiency and agronomic efficiency of fertilizer at mature oil palm – a review / Norsahira Mohd Sidik - Mohd Sidik, Norsahira (Faculty of Plantation and Agrotechnology, 2017)
This review is about the nutrient use efficiency in the mature oil palm. The efficiency is defined as the amount of product produced per unit of resource used. There are three type of efficiency which are 1) agronomic efficiency (AE), 2) physiological efficiency (PE), 3) apparent recovery efficiency. This review only focuses on PE and AE of fertilizer that affect the mature oil palm. The nutrient from fertilizer that is taken by the palm tree is the macro nutrient such as N, P, K and Mg. The nutrient can be loss through a few factors which are leaching, nitrogen volatilization and nutrient fixation. These factors contribute to the plant uptake and manager must know the amount of the fertilizer requirement using the equation of the PE and AE. The increased yield per unit of nutrient applied known as AE. From the practical view of agronomists can predict potential yield based on the nutrient applied and uptake which can be helpful in determining the oil palm fertilizer requirement. PE result can also be used to identify and evaluate problem fields in oil palm plantation. Then, it also discuss the best placement of the fertilizer is under the soil beneath frond stack and the right timing for application of fertilizer is during the production of bunches and avoid during the high probability of rainfall distribution.